The dance of reality - Jodorowsky, Adan 1979- (Curzon Film World Limited, 2015)
A mystical autobiography of Alejandro Jodorowsky's childhood that blends his personal history with metaphor, mythology, and poetry. It reflects his philosophy that reality is not objective, but rather a "dance" created by our own imaginations
Bildformat 1.85:1
Original: Chile, Frankreich, 2013
Special features: Cannes introduction with cast and crew and Nicolas Winding Refn, Trailer
Keywords: Film; DVD-Video